Chiral Switch of Gadopiclenol: New Standards in MRI Probes - Roberta Napolitano; Nicol Guidolin; Mariangela Boccalon; Alberto Fringuello Mingo; Sonia Colombo Serra; Federica Buonsanti; Roberta Fretta; Nicola Demitri; Attila Bényei; Mauro Botta; Giovanni Battista Giovenzana; Fabio Tedoldi; et al. (Advanced Science)
Abstract Magnetic Resonance Imaging (MRI) plays a vital role in the accurate diagnosis of numerous human diseases and disorders, with Gd(III)‐based contrast agents (GBCAs) being used in ≈30%–40% of procedures, resulting in ≈30 million doses administered annually worldwide. The careful design of a rigid macrocyclic chelator featuring a highly hydrophilic periphery leads to the development of gadopiclenol, the first bis‐hydrated Gd(III)‐based MRI contrast agent, recently approved for clinical use by both the FDA and EMA. The stereochemistry of the coordinating arms is found to play a crucial role in the remarkable thermodynamic stability and inertness of the Gd(III)‐complex with the RRR/SSS‐stereoisomer of this heptadentate chelating agent, ensuring its safety in vivo. The exceptional stability of the most effective gadopiclenol enantiomeric pair (RRR/SSS), coupled with a relaxivity 2 to 3 times higher than that of currently used GBCAs, has enabled the use of reduced doses while ensuring non‐inferior image contrast.